Financial Performance Management at PT Bank Rakyat Indonesia (Persero) Tbk Period 2018 - 2022 - Syaiful Anshori; Ainorrofiqie Ainorrofiqie; Nurul Hidayat; Hertin Khalifatun Nisa Arifah; Rahmat Zulkarnain (Institut Nurul Islam Mojokerto, 2025)
Bank financial institutions are one of the important factors for a country's economy which functions as a collector and channeler of public funds. The bank's ability to increase overall efficiency and generate profits is a reflection of the bank's good financial performance management. This research aims to analyze financial performance management at PT Bank Rakyat Indonesia (Persero) Tbk. 2018-2022 period, by analyzing the influence of Operational Costs on Operating Income (BOPO), Non-Performing Loans (NPL) And Loans deposit Ratio (LDR) to Return On Assets (ROA). The data used in this research is the Time Series of PT quarterly report data. Bank Rakyat Indonesia (Persero) Tbk. Which recorded in data FSA period first quarter 2018- quarterly IV 2022, with data analysis techniques Which used is multiple linear regression using SPSS version 26. The results of the research show that both partial and simultaneous costs Operational Operating Income (BOPO), Non Performing Loans (NPL), Loan Deposits Ratio (LDR) has a significant effect on Return On Assets (ROA) on PT. People's Bank Indonesia (Persero) Tbk.